2018
DOI: 10.5312/wjo.v9.i9.138
|View full text |Cite
|
Sign up to set email alerts
|

Single rod instrumentation in patients with scoliosis and co-morbidities: Indications and outcomes

Abstract: AIMTo present our results on the use of a single rod instrumentation correction technique in a small number of patients with major medical co-morbidities.METHODSThis study was a prospective single surgeon series. Patients were treated with single rod hybrid constructs and had a minimum 2-year follow-up. Indications included complex underlying co-morbidities, conversion of growing rods to definitive fusion, and moderate adolescent idiopathic primarily thoracic scoliosis with severe eczema and low body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…In the case of complications, where revision is required, this posterior approach has numerous other advantages—in the case of coronal or sagittal over-correction, with a minor procedure under local anaesthetic in most cases, you are able to cut the tether at the different levels you intended to. In the case of unacceptable under-correction or curve progression, you are able to approach the spine through the same skin incision and perform a posterior spinal instrumented fusion with concave side instrumentation only, which has been shown to achieve good results [ 40 ]. In the case of screw pull-out or loosening or a broken tether that requires revision, everything can be performed from the posterior approach as a less invasive procedure with no majors risks or concerns.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of complications, where revision is required, this posterior approach has numerous other advantages—in the case of coronal or sagittal over-correction, with a minor procedure under local anaesthetic in most cases, you are able to cut the tether at the different levels you intended to. In the case of unacceptable under-correction or curve progression, you are able to approach the spine through the same skin incision and perform a posterior spinal instrumented fusion with concave side instrumentation only, which has been shown to achieve good results [ 40 ]. In the case of screw pull-out or loosening or a broken tether that requires revision, everything can be performed from the posterior approach as a less invasive procedure with no majors risks or concerns.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent systematic review, the majority of published reports regarding unilateral instrumentation for degenerative spine conditions involved only a single lumbar level [ 11 ]. The use of unilateral pedicle screw instrumentation for spine deformity has been described by Tsirikos et al who reported a single-center series of multi-level unilateral instrumentation (pedicle screws/hook-rod construct) for scoliosis with minimal complications in selected patients [ 12 ]. The same group has also reported the use of low-density pedicle screws on the concavity of the curve (proximal/distal aspect of the construct) and instrumenting most levels on the convexity of the curve [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tsirikos et al [28] Kim et al [31] провели сравнительный анализ результатов хирургического лечения 52 подростков с идиопатическим сколиозом. Все пациенты были разделены на 2 равные группы в зависимости от применяемой техники хирургического вмешательства.…”
Section: результатыunclassified